Analisis Flypaper Effect, Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU) dan Dana Alokasi Khusus (DAK) terhadap Belanja Daerah Kabupaten/Kota di Provinsi Jawa Barat 2017-2021 - Apriliani, Desi; Sudjana (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study is to determine the partial and simultaneous effects of local revenue (PAD), general allocation fund (DAU), and special allocation fund (DAK) on regional expenditure, as well as to provide empirical evidence of whether the flypaper effect occurs in the districts and cities of West Java Province from 2017 to 2021. This is a quantitative research study with a sample of 27 districts and cities in West Java Province. The data source for this study is secondary data obtained from the website of the Government Financial Agency (BPK). The results of the study indicate that (1) PAD has a positive and significant effect on regional expenditure, (2) DAU has a positive but not significant effect on regional expenditure, (3) DAK has a positive and significant effect on regional expenditure, (4) PAD, DAU, and DAK have a positive and significant simultaneous effect on regional expenditure, and (5) there is no flypaper effect phenomenon in the districts and cities of West Java Province from 2017 to 2021.